(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
The impact of climate change in developing countries such as prolonged droughts, flooding and erratic rainfall, among other effects are increasingly driving agricultural-dependent households into deeper poverty each year. Addressing these challenges requires comprehensive adaptation and mitigation strategies, involving both local and global efforts. Self-help groups (SHGs) are recognized as powerful instruments for the empowerment of vulnerable groups, particularly women, by providing access to credit and health information. They also play a crucial role in climate change adaptation and mitigation, which in turn enhances sustainable livelihoods for their members. However, this aspect has received limited attention in academic research. This study explores the nexus between SHGs, climate change mitigation, and sustainable livelihoods in Nyakach Sub County, a region where persistent poverty is exacerbated by recurrent climate shocks. A descriptive research design was employed, involving a sample of 384 respondents selected from members of 630 self-help groups (SHGs) in Nyakach Sub County, Kenya. The study’s findings show that SHG members benefit from SHGs facilitated capital assets some of which that have not only led to reduced reliance on firewood, thus mitigating deforestation, but also facilitated a transition to alternative energy sources. This shift has enhanced their adaptive capacity to challenges posed by climate change. Furthermore, a significant correlation (rs=0.659, p=0.014) was observed between SHG-associated resources and competencies in climate change mitigation, as well as household sustainability. Additionally, collective action, such as participation in tree planting and trenching/water channelling to combat flood effects, showed a strong correlation with SHG-associated resources. Overall, the study concludes that SHG-linked assets and competencies play a vital role in enhancing climate change adaptation and the sustainable livelihoods of members. The study recommends increased emphasis on strengthening social capital within SHGs.